Characterization of cognitive functioning in complex PTSD compared to non-complex PTSD - Schöndorf, Zoe-Sofia; Terhoeven, Valentin; Jähn, Anna; Roesch-Ely, Daniela; Friederich, Hans-Christoph; Nikendei, Christoph; Kindermann, David (Frontiers in psychiatry, 2024)
BackgroundPrevious research has indicated cognitive impairments in patients with post-traumatic stress disorder (PTSD), specifically in attention, memory, and executive functioning. However, there is limited knowledge about the cognitive profile of individuals with complex PTSD (cPTSD), a new diagnosis in ICD-11. Moreover, predictors of cognitive impairment remain unclear. The present study aims to enhance understanding of cognitive functioning and its predictors in cPTSD compared with non-complex PTSD (ncPTSD).MethodsN = 64 participants (n = 34 cPTSD, n = 30 ncPTSD) completed psychometric questionnaires and the neuropsychological test set Cognitive Basic Assessment (COGBAT) assessing a general cognitive index, attention, visual memory, and executive functioning. First, the test results of both groups were compared to the COGBAT norm sample. Secondly, group differences in cognitive domains were analyzed using student t-tests with independent samples (cPTSD vs. ncPTSD). Thirdly, bivariate and multivariate regressions examined influencing factors of cognitive impairment.ResultsBoth groups showed cognitive impairments in comparison to the COGBAT norm group. Significant differences between cPTSD and ncPTSD were found in visual memory (p = .003) and selective attention (p = .004). In multivariate regression, type of PTSD and age were found to significantly impact visual memory, while type of PTSD, age, and psychotropic medication showed significant effects on selective attention.ConclusionsGiven higher symptom severity and cognitive deficits in cPTSD, more intensive and diverse interventions should be considered in comprehensive treatment plans, for instance, cognitive training.
Online veröffentlicht: 15. Januar 2025
Gesehen am 25.08.2025